Understanding Climate Change Material through Immersive Virtual Learning (IVL) - Gusti Rusmayadi; Marsella Desriyarini; Nelli Roza; Asita Al Mufida (Jurnal Penelitian Pendidikan IPA, 2023)
Immersive Virtual Learning is learning that is considered meaningful for students to study climate change material which is considered complex because of the many interactions between the systems involved in it, and is considered to be material that is quite challenging for students. It is known that there are still many students who have limited knowledge about climate change so that learning methods are needed that can help them understand the climate change material well. This study aims to see how students' understanding after learning using the Immersive Virtual Learning (IVL) learning method, compared to the understanding of students using conventional learning methods. Using the Pre-Post Experiment Control Group Design design and involving 59 students who were divided into treatment and control classes, produced research data showing that students' understanding in the two classes experienced significant differences in improvement, but the increase in question was very small, even though the class treatment experienced a better increase than the control class. Based on this, it can be concluded that students' understanding has increased slightly after learning to use the Immersive Virtual Learning method. Further research is needed to develop the IVL method in order to provide better learning outcomes.